El último adiós a Massino Pavarini, el encuentro en su casa en Bologna, junto a Eugenio Raúl Zaffaroni - Croxatto, Guido Leonardo (2015)
Fil: Croxatto, Guido Leonardo. Universidad de Buenos Aires. Facultad de Derecho. Buenos Aires, Argentina